Definition of a project performance indicators model: contribution of collaborative engineering practices on project management - Pereira, Marcelo Silva (2018)
Monitoring and controlling the progress of project activities are important processes for managers, because allow them identify the limits which may compromise the project progress, comparing the current situation with elaborate planning and consequently assisting the managers to balance the project activities and put them according to the initial plan. To support the needs of project monitoring and controlling, the PMI-Project Management Institute-indicates a process set described on the PMBok-Project Management Body of Knowledge-which assists the project managers during their activities. Not all activities described in the PMBoK relates in a collaborative way all the involved in a project (collaborators, stakeholders, providers). Considering the need for collaboration, this work intends to contribute to answer to the following questions: how to create conditions to collaboration among the involved in projects through of project management? What techniques and tools can be used to create conditions of collaborative engineering inside of projects? Therefore, in this paper tools and techniques for monitoring and controlling of project management practices are compared with collaborative engineering practices based on systematic literature review. Furthermore, supported by this comparison a project performance indicators model approach for monitoring and controlling of project performance is presented.